2012
DOI: 10.1080/17588928.2012.674935
|View full text |Cite
|
Sign up to set email alerts
|

More than a feeling: Pervasive influences of memory without awareness of retrieval

Abstract: The subjective experiences of recollection and familiarity have featured prominently in the search for neurocognitive mechanisms of memory. However, these two explicit expressions of memory, which involve conscious awareness of memory retrieval, are distinct from an entire category of implicit expressions of memory that do not entail such awareness. This review summarizes recent evidence showing that neurocognitive processing related to implicit memory can powerfully influence the behavioral and neural measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
110
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(118 citation statements)
references
References 92 publications
6
110
2
Order By: Relevance
“…Additionally, we suggest that the probability of correctly selecting a target item with zero confidence varied with the overall difficulty of the particular recognition test, and a concurrent shift in the criterion associated with the subjective feeling of what constitutes a "guess" response. Voss and Paller (2012) suggest that their effects are based on fluency of perceptual processing of the encoded representations, and this seems very reasonable given that the items were complex and relatively meaningless visual patterns. In the present case, the correct selection of the target word when confidence was zero may also be attributable to the greater perceptual fluency of processing targets relative to lures (Jacoby and Whitehouse (1989).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, we suggest that the probability of correctly selecting a target item with zero confidence varied with the overall difficulty of the particular recognition test, and a concurrent shift in the criterion associated with the subjective feeling of what constitutes a "guess" response. Voss and Paller (2012) suggest that their effects are based on fluency of perceptual processing of the encoded representations, and this seems very reasonable given that the items were complex and relatively meaningless visual patterns. In the present case, the correct selection of the target word when confidence was zero may also be attributable to the greater perceptual fluency of processing targets relative to lures (Jacoby and Whitehouse (1989).…”
mentioning
confidence: 94%
“…Such instances were documented both by Voss and colleagues and in the present experiments. Voss and Paller (2010) consider, but reject, the possibility that recognition without awareness is simply based on the processing of relatively weak representations that might otherwise evoke responses of familiarity or recollection (see also Voss, Lucas & Paller, 2012). Their arguments are based partly on different ERP signatures related to implicit memory compared to those associated with familiarity and recollection (Voss et al, 2012), but also to the changes in R, K, and guess responses between conditions in This article is intended solely for the personal use of the individual user and is not to be disseminated broadly.…”
mentioning
confidence: 99%
“…Others have suggested that fluency signals are implicit in nature and therefore separate from familiarity, but may (accidentally) contaminate explicit forms of memory, i.e. familiarity-based recognition (for a similar line of argument, see Lucas, Taylor, Henson, & Paller, 2012;Voss, Lucas, & Paller, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Like the N400, FN400 is a negative deflection which develops between 300 and 500 ms after stimulus onset, but unlike the N400, FN400's maximal amplitude is usually at frontal/ fronto-central sites. The functional significance of this ERP component is still debated, with some investigators contending that it reflects familiarity-based recognition (reviewed in Curran, Tepe, & Piatt, 2006;Rugg & Curran, 2007), but others proposing that it instead reflects conceptual priming (Voss, Lucas, & Paller 2012), similar to the centro-parietal N400 (Voss & Federmeier, 2011) . We included relevant frontal sites in our N400 analyses to explore the potential presence of FN400 and generate hypotheses about its role.…”
Section: Introductionmentioning
confidence: 99%